(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Swadesh Darshan is a prestigious scheme of the Ministry of tourism, India has a variety of resources and there is need to develop major tourist circuits on specific themes to attract the tourists having the special interest in visiting such places. Under this scheme, only Kurkshetra is selected under Krishna circuit. The state Haryana has the potential of tourism due to its location and resources. This paper concludes the relationship between Swadesh Darshan scheme and tourist destination of Haryana.